Diffusion functional MRI reveals global brain network functional abnormalities driven by targeted local activity in a neuropsychiatric disease mouse model - Yoshifumi Abe; Norio Takata; Yuki Sakai; Hiro Taiyo Hamada; Yuichi Hiraoka; Tomomi Aida; Kohichi Tanaka; Denis Le Bihan; Kenji Doya; Kenji F Tanaka (NeuroImage, 2020)
Diffusion functional magnetic resonance imaging (DfMRI) has been proposed as an alternative functional imaging method to detect brain activity without confounding hemodynamic effects. Here, taking advantage of this DfMRI feature, we investigated abnormalities of dynamic brain function in a neuropsychiatric disease mouse model (glial glutamate transporter-knockdown mice with obsessive–compulsive disorder [OCD]-related behavior). Our DfMRI approaches consisted of three analyses: resting state brain activity, functional connectivity, and propagation of neural information. We detected hyperactivation and biased connectivity across the cortico-striatal-thalamic circuitry, which is consistent with known blood oxygen-level dependent (BOLD)-fMRI patterns in OCD patients. In addition, we performed ignition-driven mean integration (IDMI) analysis, which combined activity and connectivity analyses, to evaluate neural propagation initiated from brain activation. This analysis revealed an unbalanced distribution of neural propagation initiated from intrinsic local activation to the global network, while these were not detected by the conventional method with BOLD-fMRI. This abnormal function detected by DfMRI was associated with OCD-related behavior. Together, our comprehensive DfMRI approaches can successfully provide information on dynamic brain function in normal and diseased brains.